Pengembangan Media Big Book Digital Untuk Mendukung Kemampuan Membaca Siswa Kelas II SDN 28 Banyuasin I - Febriyana, Lala; Hodsay, Zahruddin; Aldora Pratama (Jurnal keilmuan dan Kependidikan dasar, 2025)
The aim of this study is to develop digital Big Book-based instructional media specifically designed for Grade II elementary school students, incorporating relevant learning content. The development model employed in this research is the ADDIE model, which consists of five stages: Analyze, involving analysis of the background, concepts, and learning resources; Design, the stage of designing the instructional media product; Development, which includes media development and validation by subject matter experts, language experts, and media experts; Implementation, the stage where the developed media is implemented with students, including the use of questionnaires; and Evaluation. The validation results showed that the product received a 96% score from content experts, 81% from language experts, and 96% from media experts, indicating that the media is feasible and valid for use.  Based on these findings, it can be concluded that the developed media is suitable for use in the learning process of Grade II elementary school students.